The implementation of safety management at factory buildings in Shah Alam / Nor Nia Kuzairah Kassim - Kassim, Nor Nia Kuzairah (Faculty of Architecture, Planning and Surveying, 2013)
Manufacturing industry is one of the industries that contribute to a greater economic growth. However, it is also exposed to risks and injuries as it involve a big machineries and equipment. Issue and cases on accident or fire at factory every year cause a chaotic and common phenomenon in Malaysia manufacturing industry. Thus, it forced the government to investigate and find a solution to reduce the percentage of accident relating factory. As a result, Factories and Machinery Act was established in 1967 as a guideline to employer and related individuals. This research is to study and focused on implementation on safety management at factory, in term of safety measure apply by employer at his/her factory in Shah Alam industrial area. This study shall include literature review, followed with observation on case study, distribution questionnaire to selected employees, and through interview session with factory’s safety officer who involved in safety implementation at factory. The aim of this research is first, to highlight on the implementation of safety management in factories at Shah Alam. This study also will focus on the guidelines provided by Factory and Machineries Act, 1967. To achieve this aim, several objectives have determined and will be analyzed after study has been conducted. Lastly, safety management is applying at factory by rules and regulation, monitoring and control, safe work practise and safety policy. Safety measures can be implemented by four (4) methods, namely safety training, safety promotion, group meetings and emergency preparedness.